Tinjauan Yuridis Terhadap Perjanjian Pemisahan Harta dalam Perkawinan Pasca Putusan Mahkamah Konstitusi Nomor 69/PUU-XIII/2015 - Lutfiana Dwi Mayasari; Abid Rohmanu (Institut Agama Islam Negeri Ponorogo, 2022)
The issuance of the Constitutional Court's decision Number 69/PUU-XIII/2015 aims to provide asset ownership rights for Indonesian citizens married to foreigners. However, this decision has an impact on simultaneous regulatory changes. Both in the body of the Marriage Law itself and the executorial institution making the marriage agreement. This type of research is normative juridical research with a statute approach. The nature of the study is descriptive and analytical, while the analysis of legal materials is carried out qualitatively. The theoretical basis used is the theory of harmonisation and synchronisation of law and the theory of legal principles by Hans Kelsen. From the study results, it was concluded that according to Hans Kelsen's theory of norm hierarchy, the decision of the Constitutional Court Number 69/PUU-XIII/2015 had an impact on the emergence of legal dualism. For the conclusion of the Constitutional Court Number 69/PUU-XIII/2015 to be implemented, an effort is needed to harmonise the rules both vertically and horizontally.